POSITIVISASI” HUKUM ISLAM DALAM UNDANG-UNDANG PERBANKAN SYARIAH DI INDONESIA - Zuliansyah, Ahmad (ASAS, 2011)
Abstak: The application of Islamic law in the activities of banking / finance or other modern economic activities is                not          a simple    job. The    study    of    the    banking     law,    or sharia financesharia law to be an interesting study and challenging for the world of law in Indonesia where the positive law (law) in the country of Indonesia is different from that applicableto the religious law (Islam). Enforcement of religious law     (Islam)                  must go through a process referred to as the "positivisasi" Islamic law. In this case, Islamic law acceptedby the state in positive laws and regulations that apply nationally. This paper will examine the law of Law no. 10 of 1998 concerning Amendment to law number 7 of 1992. Likewise, Law number 21 of         2008 has         some         interesting general provisions to         be         observed. General provisions referred to (Article 1) is a novelty and will provide certain implications. Keywords: Islamic bank, Undang-Undang Perbankan Syariah.